2016
DOI: 10.3897/italianbotanist.1.8647
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional IUCN Red List Assessments: 1

Abstract: In this contribution, the conservation status assessment of six plant species according to IUCN categories and criteria are presented. It includes the assessment at global level of Linaria tonzigii Lona, Allium garganicum Brullo, Pavone, Salmeri & Terrasi, Ferula arrigonii Bocchieri, Orchis patens Desf. subsp. patens and Armeria saviana Selvi and the assessment at regional level (Italy) of Viola jordanii Hanry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It occurs in an extremely restricted range (convex hull of about 10 km 2 ) and is found in unstable and dynamic habitats characterized by incoherent accumulations of coarse gravel in particularly steep mountain screes (Giupponi and Giorgi 2019). It usually occurs in the alpine and subalpine altitudinal planes and exclusively on calcareous substrates (Orsenigo et al 2016). The plant is about 6-12 cm tall, each stalk usually hosts 3-6 (rarely 10) single flowers, and the flowering phenology lasts from around mid-June to mid-July, with some individuals flowering earlier or later in the season.…”
Section: Methodsmentioning
confidence: 99%
“…It occurs in an extremely restricted range (convex hull of about 10 km 2 ) and is found in unstable and dynamic habitats characterized by incoherent accumulations of coarse gravel in particularly steep mountain screes (Giupponi and Giorgi 2019). It usually occurs in the alpine and subalpine altitudinal planes and exclusively on calcareous substrates (Orsenigo et al 2016). The plant is about 6-12 cm tall, each stalk usually hosts 3-6 (rarely 10) single flowers, and the flowering phenology lasts from around mid-June to mid-July, with some individuals flowering earlier or later in the season.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the publication of new plant species frequently includes an assessment of their status based on the IUCN criteria. Although some Italian endemic taxa have been recently assessed against the IUCN criteria (e.g., Foggi et al, 2014;Rossi et al, 2016;Orsenigo et al, 2016Orsenigo et al, , 2017Fenu et al, 2016Fenu et al, , 2017a, a comprehensive Red List for the Italian endemic vascular plants is still lacking. The evaluation of the extinction risk of all the Italian endemic plants would provide a powerful tool for driving further conservation steps for these unique organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, we want to highlight the conservation relevance of plant communities with Cirsium alpislunae. As already done for other endemic Tuscan and Italian species (Foggi et al, 2015;Orsenigo et al, 2016;Fenu et al, 2016Fenu et al, , 2017 this thistle was already globally assessed with the IUCN methods and found to have a Near Threatened (NT) status (Gennai et al, 2015). Laserpitio latifolii-Cirsietum alpis-lunae conenoses are also important, because they too are strictly endemic and because they can be attributed to a Natura 2000 habitat type of European conservation interest, i.e.…”
Section: Resultsmentioning
confidence: 89%